Unidades de saúde pública em Curitiba: uma análise exploratória e um protótipo de dashboard de saúde para apoio à decisão no domínio da gestão em saúde - Lautert, Tatiane Araujo Muniz (2020)
Guaranteeing adequate health services to the population is a challenge, especially in developing countries where limited resources must be optimized in order to reach a larger percentage of the population. To properly assess health services and prioritize new investments, it is important to collect, integrate, and analyze large amount of relevant data. This dissertation presents a study aggregating publicly available sócio-environmental, sócio-economic, geographical, transportation, and health data from different sources for the city of Curitiba in Brazil, to understand the dynamics of current healthcare needs and healthcare usage by the city dwellers. This dissertation presents a detailed analyses on medical appointments, the neighborhood where patients come from, the most frequent health conditions reported from the medical assistance records. We also analyze the onset of certain infectious diseases in the city’s neighborhoods and correlations between these diseases with various sócio-environmental and sócio-economic factors. Finally, the dissertation discusses the findings from our exploratory analysis, highlighting possible points deserving special attention or investments from the city management to better serve the public.